PREDIÇÃO NUMÉRICA DO CONTROLE MECÂNICO NA DINÂMICA POPULACIONAL DOS MOSQUITOS DA DENGUE - SILVA, Lucas Romero Galvão; SANTOS, Fernando Luiz Pio dos (Brazilian Journal of Biometrics, 2018)
In this work we investigated the dynamic of dengue mosquitoes with mechanical control applied in the aquatic phase. The mathematical model describes the dynamic of dengue mosquitoes in the immature and winged phases. This model is based on a system of nonlinear ordinary diferential equations (ODE). The mechanical control is modelled by an ODE coupled to the system and applied in the aquatic phase. In order to obtain the numerical solutions, the system was discretized using the nite diference method. Computational simulations considering the absence of control and the efective control of the mosquitoes were performed. The numerical results were presented and show the efects of the control in the dynamic of dengue mosquitoes.